1989
DOI: 10.1152/ajpcell.1989.256.3.c569
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of TPA and insulin on Na+ transport across frog skin

Abstract: The phorbol ester 12-O-tetradecanoylphorbol 13-acetate (TPA) activates protein kinase C (PKC) and produces an early stimulation of Na+ transport across frog skin. The ionic basis for this stimulation was studied with combined transepithelial and intracellular electrical measurements. In an initial series of experiments, TPA approximately doubled the amiloride-sensitive short-circuit current (ISC), apical Na+ permeability (PapNa), and apical membrane conductance without affecting the basolateral membrane conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…We have previously reported that PKC activation inhibits the subsequent natriferic response to cAMP (Civan et al, , 1989Mauro et al, 1987). In the present study, we have found that reducing Ca 2+ cytosolic entry from the extracellular fluid or from the endoplasmic reticulum reduces the PKC-triggered natriferic response.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…We have previously reported that PKC activation inhibits the subsequent natriferic response to cAMP (Civan et al, , 1989Mauro et al, 1987). In the present study, we have found that reducing Ca 2+ cytosolic entry from the extracellular fluid or from the endoplasmic reticulum reduces the PKC-triggered natriferic response.…”
Section: Introductionsupporting
confidence: 60%
“…PKC stimulates Na + transport across frog skin epithelium by as much as 40-60% (Civan et al, 1989). The natriferic action appears to reflect an increase in Pa~P a (Civan et al, , 1989.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although it has been disputed, PKC has been proposed as a mediator for some effects of insulin (e.g. hexone transport [ 12], lipogenesis [13], sodium trans port [14] and glucose carrier translocation [15]). On the other hand, tumor-promoting esters (e.g.…”
mentioning
confidence: 99%